2006
DOI: 10.1111/j.1468-3083.2006.01693.x
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase gene expression in oral lichen planus: erosive vs. reticular forms

Abstract: The different clinical appearances of OLP are associated with significant differences in MMP mRNA levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 26 publications
1
26
0
3
Order By: Relevance
“…15 The process from OLP to OSCC is complicated and regulated by many factors. 15 Erosive form is more susceptible than reticular to malignant transformation, Our results confirm this process well and support the earlier report by Mazzarella et al, 20 It may mean that if we screen the MMP-3 in OLP periodically, its rises may indicate a signal toward malignant transformation. This would be very important for both patients and clinician.…”
Section: Discussionsupporting
confidence: 92%
“…15 The process from OLP to OSCC is complicated and regulated by many factors. 15 Erosive form is more susceptible than reticular to malignant transformation, Our results confirm this process well and support the earlier report by Mazzarella et al, 20 It may mean that if we screen the MMP-3 in OLP periodically, its rises may indicate a signal toward malignant transformation. This would be very important for both patients and clinician.…”
Section: Discussionsupporting
confidence: 92%
“…it is still not generally accepted, that olp bears the malignant potential and these results might bring more understanding in malignant transformation of olp. on the other hand, Mazzarella et al (23) reported higher levels of MMp -9 in reticular olp than in erosive olp. erosive form of olp is however believed to be more aggressive variant of the disease.…”
Section: Resultsmentioning
confidence: 93%
“…Karatsaidis (2004) • Aumento de núcleos TUNEL+ de linfocitos T CD4 y CD68. Mazzarella (2006) • MMP-1 y 3 mayores en la forma erosiva respecto a la reticular . Karatsaidis (2003) • Ausencia de apoptosis.…”
Section: Estudio Clínico Resultadosunclassified
“…Sugieren que la alteración de la diferenciación de queratinocitos y/ o de su muerte celular programada sería la causa de la aparición de las lesiones de LPO. 17 (2006) sugieren la implicación de una familia de proteinasas zinc-dependientes, las metaloproteinasas de matriz (MMP), relacionadas con los procesos necesarios para la remodelación tisular, la curación de heridas y la invasión tumoral como son la angiogénesis, la migración celular y la activación proteolítica de factores de crecimiento. La actividad de las MMP se regula por los inhibidores endógenos tisulares de metaloproteinasas (TIMP), implicados por tanto en procesos como la proliferación y apoptosis celular y procesos angiogénicos e inflamatorios.…”
Section: Discussionunclassified